Trichotilomanìa in a adolescent during the COVID-19 pandemic. Case report - Huete-Cordova, María Antonieta (2022)
Trichotillomania is a disorder that tends to be chronic and consists of pulling and pulling hair as a compulsive act, which generates various areas of alopecia. In extreme cases after chronic ingestion of hair, severe and serious gastrointestinal disorders such as trichobezoars can be generated, which represents 1% of patients who eat their hair. We present the case of an 11-year-old female patient who was admitted to our hospital for a trichobezoar intestinal obstruction that was initially managed by surgery, from which she was referred to the child psychiatry area, once the surgical problema had been solved, for the corresponding management.